(untitled) (Research, Society and Development, 2022)
With the increase in the production of agricultural waste becomes the use of processes that is important for the production of organic or organic nutrients. This way, the objective was to use ecomposts, composed from aquatic macrophytes in the agricultural production of (Zea mays L.) corn and to evaluate the biometric and productive performance of the plants in response to organic triggering. The silting experiment at the São Paulo State University of Ilha Sol Farm. There were two composts based on aquatic macrophytes, one composted and the other vermicomposted. The Montado was in a randomized block design, with eight treatments, three days with three composite compounds – 20, 40, 60 days – 20, 40, 60, one with NPK fertilization and one without fertilization, containing 10 useful plants in each plot. The efficient composts were composed for and corn productivity, not presenting the types of growth only for the magnitude and the average number of grains per highlight and, for the composting time only for height, abundance and average number of grains in full and average number of des per ear. Between the control treatment (Soil) and the control (NPK) only grain moisture showed no statistical difference between treatments. These results show the potential of the aquatic macrophyte as an organic vermicompost fertilizer, with the best result being 60 days of composting.